2005
DOI: 10.1021/jp0478209
|View full text |Cite
|
Sign up to set email alerts
|

Modification and Stability of Aromatic Self-Assembled Monolayers upon Irradiation with Energetic Particles

Abstract: We have studied ion and electron irradiation of self-assembled monolayers (SAMs) of 2-(4'-methyl-biphenyl-4yl)-ethanethiol (BP2, CH3-C6H4C6H4CH2CH2-SH), phenyl mercaptan (PEM, C6H5CH2CH2-SH), and 4'-methyl-biphenyl-4-thiol (BP0, CH3-C6H4C6H4-SH) deposited on Au(111) substrates. Desorption of neutral particles from PEM/Au and BP2/Au was investigated using laser ionization in combination with mass spectrometry. The ion-induced damage of both BP2 and PEM SAMs is very efficient and interaction with a single ion le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
49
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 72 publications
3
49
0
Order By: Relevance
“…Herein we propose using ion‐induced desorption in combination with neutral fragment mass spectrometry as a method to analyze the chemical stability of the molecule–substrate interface in complicated and technologically relevant SAMs. This work builds on previous studies analyzing the behavior of SAMs on a Au(111) substrate upon bombardment with beams of Ar + ions in the keV range 58. It was shown that the bombardment of aromatic thiol SAMs on a Au(111) substrate results in the ejection of neutral molecular fragments via two distinct desorption mechanisms.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Herein we propose using ion‐induced desorption in combination with neutral fragment mass spectrometry as a method to analyze the chemical stability of the molecule–substrate interface in complicated and technologically relevant SAMs. This work builds on previous studies analyzing the behavior of SAMs on a Au(111) substrate upon bombardment with beams of Ar + ions in the keV range 58. It was shown that the bombardment of aromatic thiol SAMs on a Au(111) substrate results in the ejection of neutral molecular fragments via two distinct desorption mechanisms.…”
mentioning
confidence: 63%
“…Finally, we note that in the presented method, chemical reactions of reactive molecular fragments produced by the primary ion impact probe the chemical stability of the molecule–substrate bonding in SAMs. Since a low dose of primary ions (∼10 10 ions/cm 2 , see the Experimental Section) is used for this analysis (static conditions), and the produced reactive species quickly move out of the primary ion impact zone,8 the proposed method analyzes, fast and locally, the unperturbed structure of the molecule–substrate interface in SAMs. This is in contrast to relatively slow thermal or electrochemical desorption experiments where, due to the global temperature1921, 29, 35 or potential36 ramping, respectively, the molecule–substrate interface in SAMs can reconstruct before the desorption process takes place.…”
mentioning
confidence: 99%
“…[24,25] The bombardment of aromatic thiol SAMs on a Au(111) substrate with beams of Ar + ions in the keV range results in the ejection of neutral molecular fragments via two distinct desorption mechanisms. [24,[26][27][28][29] A small percentage of the SAM fragments is desorbed with high kinetic energies (~eV) as a result of the direct momentum transfer from the collision cascade that develops in the substrate upon primary ion impact. The majority of desorbing particles, however, leaves the surface with low kinetic energies (~10 À2 eV) as a result of gentle (i.e.…”
mentioning
confidence: 99%
“…Performing photon-fluence dependence measurements on gas-phase molecules demonstrated that the fragment m/z 168, the desulphurized molecule (BPnS -S), and the parent molecule (BPnS) are direct products of the ion-induced desorption process, while the other molecular fragments, including m/z 181, at least partly stem from photofragmentation of larger molecular entities. [24,25,29] A normalization of the mass spectra is necessary in order to correct for small experimental variations between the different sets of measurements. For normalization we use the total detected amount of desorbed molecular material with low kinetic energy.…”
mentioning
confidence: 99%
“…Ar + , Ga + , Si + , etc. ), which leads to the desorption and the fragmentation of molecules [1415]. High energy helium ions passing through polymer films modify the macroscopic properties of these films, too.…”
Section: Introductionmentioning
confidence: 99%